Effect of Aging Time and Film Thickness on the Photoelectrochemical Properties of TiO2 Sol-Gel Photoanodes - D. Regonini; A. K. Alves; F. A. Berutti; F. Clemens (International Journal of Photoenergy)
This work has focused on the investigation of a non-aqueous based sol-gel process to produce TiO2 based photoelectrodes for solar water splitting. In particular, the effect of the aging time of the sol and TiO2 film thickness on the photoelectrochemical properties of the photoanodes has been investigated. In order to achieve optimal performances (i.e., photocurrent density up to 570 µA/cm2 and IPCE of 26% at 300 nm), the sol needs to be aged for 3 to 6 h, before being dip-coated to produce the photoanodes. The importance of the aging time can also be appreciated from the optical properties of the TiO2 films; the absorbance threshold of the sol-gel aged for 3–6 h is slightly shifted towards longer wavelenghts in comparison to 0 h aging. Aging is necessary to build up a well-interconnected sol-gel network which finally leads to a photoelectrode with optimized light absorption and electron collection properties. This is also confirmed by the higher IPCE signal of aged photoelectrodes, especially below 340 nm. Among thicknesses considered, there is no apparent significant difference in the photoresponse (photocurrent density and IPCE) of the TiO2 sol-gel films.